Achieving Sustainable Development Goals Through Curriculum Innovation and Development - Ahmad Garba (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2024)
Sustainable development is a critical global objective, addressing the need for economic, social, and environmental progress without compromising future generations' ability to meet their needs. Previous studies have highlighted the importance of education in fostering sustainable development, yet gaps still need to be in integrating sustainable development principles effectively within educational curricula. This research investigates the integration of educational tracks focused on sustainable development into curricula as a means to address this gap. The study examines explicitly how curricula that promote knowledge, values, and skills related to sustainable development can be designed and implemented to prepare students for the challenges of the modern world. A qualitative research approach was employed, using case studies of various educational systems that have successfully integrated sustainability into their curricula. Data collection involved document analysis and interviews with educators and curriculum developers. The thematic analysis examined how these curricula address economic, social, and environmental challenges. The findings demonstrate that integrating sustainable development into educational tracks significantly enhances students' awareness and capabilities in addressing sustainability issues. Moreover, it equips them with the critical thinking skills and innovative problem-solving abilities necessary for sustainable progress. The study concludes that well-designed curricula focusing on sustainable development are vital in preparing future generations to contribute meaningfully to achieving global sustainability goals.